Effect of estrogens on the binding capacity of specific proteins of animal sera - ΠΑΠΑΝΑΣΤΑΣΙΟΥ, Α.; ΜΑΝΤΖΟΣ, Ι.; ΠΙΤΣΙΝΙΔΗΣ, Γ.; ΠΑΠΑΔΟΠΟΥΛΟΣ, Ε.; ΕΥΣΤΑΘΙΟΥ, Λ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The effect of estrogens (diethylstibestrol and estradiol benzoate) on the binding capacity of specific proteins of animal sera which bind the thyroid hormones and the folic acid was studied, lor this study two sheepi two goats and two pigs used. It was found that diethlstilbestrol reduces the binding capacity of the specific proteins which bind thyroid hormones, of the sheep and goat serum and estradiol benzoate increases it. Increase was also found after the administration of both hormones to the pigs. Reduction of the binding capacity of serum specific proteins of the folic acid, was found after estrogen administration to the two pigs and the one goat. In the case of the other animals the changes in the binding capacity of folic acid were too small to be evaluated.